2015
DOI: 10.1080/09720073.2015.11891720
|View full text |Cite
|
Sign up to set email alerts
|

Professional Self-Efficacy Scale for Information and Computer Technology Teachers: Validity and Reliability Study

Abstract: This study aims at developing a valid and reliable scale to measure information and communication technology (ICT) teachers' self-efficacy related to the Turkish national framework of ICT competencies. For statistical procedures, data were respectively analyzed with exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Furthermore, test-retest procedure was carried out to confirm the time invariance of the scale. EFA results revealed that the scale's seven-factor structure accounts for 65.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A structured questionnaire with closed-ended statements with various scales on educators' self-efficacy beliefs about ICTs was developed based on instruments used in previous studies: Self-efficacy beliefs for technology integration (Wang et al, 2004;Al-Awidi and Alghazo, 2012), Self-efficacy for information and computer technology educators (Banoglu et al, 2015), and self-efficacy scale of teachers' intentions to integrate technology into their future classroom activities (Perkmen et al, 2016). The final study's instrument was an adaption and a consolidation of the instruments used in these previous studies.…”
Section: Instrumentmentioning
confidence: 99%
“…A structured questionnaire with closed-ended statements with various scales on educators' self-efficacy beliefs about ICTs was developed based on instruments used in previous studies: Self-efficacy beliefs for technology integration (Wang et al, 2004;Al-Awidi and Alghazo, 2012), Self-efficacy for information and computer technology educators (Banoglu et al, 2015), and self-efficacy scale of teachers' intentions to integrate technology into their future classroom activities (Perkmen et al, 2016). The final study's instrument was an adaption and a consolidation of the instruments used in these previous studies.…”
Section: Instrumentmentioning
confidence: 99%
“…Teachers' ICT self-efficacy scale We developed a scale to measure teachers' ICT self-efficacy (see Appendix 1) aligned with constructs of self-efficacy (Bandura, 1997), teachers' sense of efficacy scale (Tschannen-Moran and Woolfolk Hoy, 2001), computer self-efficacy (Compeau and Higgins, 1995), selfefficacy toward technology integration (Wang et al, 2004) and self-efficacy scale for ICT teachers developed by Banoglu et al (2015); consisting of 39 questions and made it standardized by the experts having an acceptable internal consistency (Cronbach's α 5 0.90).…”
Section: Research Toolsmentioning
confidence: 99%
“…In order to identify the unique contributions of WeChat utilization, several variables are controlled in the analysis, consisting of gender, age, educational level, duration of sojourn in Germany and WeChat use experience. Additionally, multiple fit indices were utilized to evaluate the overall goodness of model fit: χ 2 /df ratios be less than 3.0 (Banoglu et al, 2015), root mean square error of approximation (RMSEA) be smaller than 0.08 (Sun et al, 2017), goodness-of-fit index (GFI) and adjusted goodness-of-fit index (AGFI) be 0.8 or above (Yoo and Jeong, 2017), comparative fit index (CFI), increasing fitness index (IFI) and Tucker-Lewis index (TLI) be 0.9 or greater (Wu and Tsai, 2005). Accordingly, results indicated that the present hypothesized model fits the empirical data sufficiently well ( χ 2 /df ¼ 1.12; RMSEA ¼ 0.002; RMR ¼ 0.001; CFI ¼ 0.997; AGFI ¼ 0.925; IFI ¼ 0.978; TLI ¼ 0.966).…”
Section: Testing the Hypothesized Research Modelmentioning
confidence: 99%